Public and Private School Grade Inflations Patterns in Secondary Education - Pedro Luís Silva; Stephen L. DesJardins; Ricardo Biscaia; Carla Sá; Pedro N. Teixeira (Institute of Labor Economics (IZA), 2023)
Grade inflation in high schools is potentially problematic for students, education institutions, and society. We examine the extent of potential grading inflation in courses taken during high school and how such differences vary across student and school characteristics. Utilizing longitudinal, administrative data for the population of high school students in an entire country (Portugal) over ten years, we develop a measure of grade inflation using the position of the student's high school grade relative to their score on the national standardized admission exam. We analyze differences in this measure across four types of high schools: TEIP schools (public schools located in disadvantaged areas that include children at-risk of social exclusion), public schools (state-funded schools), private schools, and private association schools (owned by private entities but publicly funded). We find that private association schools exhibit a lower probability of grade inflation when compared to public schools. Additionally, TEIP schools tend to have a higher probability of inflation for students with high grades. Implications for policy and practice are discussed.
Keywords: I21; I23; I24; 330; grade inflation; grading standards; high school grading; postsecondary access equity; upper secondary education